Pattern of psychiatric morbidity among female patients who attended private consultation chambers in Dhaka city (Bangladesh Medical Journal, 2016)
Mental illness affect women and men differently - some disorders are more common in women; some are manifested with different symptoms. In Bangladesh, 16.1% of the adult populations suffer from some degree of mental disorder and the prevalence is higher in women than men (19.0% vs 12.9%). This study is a cross sectional study, done on female patients who attended at private chambers of psychiatrists located within Dhaka city of Bangladesh. Total sample size is 280 and duration of the study was six months from May 2014 to October 2014. The major objective of the study was to determine the pattern of psychiatric illness among the women who attended some psychiatrists private chamber in Dhaka city and also to identify the socio-economic and environmental stressors causing psychiatric illness. The findings revealed that highest numbers of the patients (41%) belonged to the age group between 21-30 years and the second largest group having 31-40 years of age (21%). Most patients hailed from urban area (79%) and among all the patients most of them were married (58%). There are various psycho-social stressors which can be held responsible for causing psychiatric illness - domestic violence, marital breakdown and co-morbid physical illness. Among the several pattern of mental diseases, depressive disorder was the commonest (17.7%), followed by somatoform disorder (14%) and schizophrenia (13.3%). Among all the patients, substance abuse was found in 4.2% of patients. This study finally argues that for reduction of psychiatric morbidity among female patients, medical services must be extended to the community level.Bangladesh Med J. 2016 Jan; 45 (1): 14-19